Essays on the informational efficiency of credit default swaps - Silva, Paulo Miguel Pereira da (2017)
This thesis contributes to the strand of the financial literature on credit derivatives, in particular the credit default swaps (CDS) market. We present four inter-connected studies addressing CDS market efficiency, price discovery, informed trading and the systemic nature of the CDS market. The first study explores a specific channel through which informed traders express their views on the CDS market: mergers and acquisitions (M&A) and divestitures activities. We show that information obtained by major banks while providing these investment services is impounded by CDS rates prior to the operation announcement. The run-up to M&A announcements is characterized by greater predictability of stock returns using past CDS spread data. The second study evaluates the incremental information value of CDS open interest relative to CDS spreads using a large panel database of obligors. We find that open interest helps predict CDS rate changes and stock returns. Positive open interest growth precedes the announcement of negative earnings surprises, consistent with the notion that its predictive ability is linked to the disclosure of material information. The third study measures the impact on CDS market quality of the ban on uncovered sovereign CDS buying imposed by the European Union. Using panel data models and a difference-in-differences analysis, we find that the ban helped stabilize CDS market volatility, but was in general detrimental to overall market quality. Lastly, we investigate the determinants of open interest dynamics to uncover the channels through which CDS may endanger the financial system. Although we find information asymmetry and divergence of opinions on firms’ future performance as relevant drivers of open interest, our results indicate that systematic factors play a much greater influence. The growth of open interest for different obligors co-varies in time and is pro-cyclical. Funding costs and counterparty risk also reduce dealers’ willingness to incur inventory risk; Eficiência dos mercados de Credit Default Swaps Resumo: Esta tese investiga o mercado de derivados de crédito, e em particular o mercado de credit default swaps (CDS). São apresentados quatro estudos interligados abordando temáticas relacionadas com a eficiência informacional, a existência de negociação informada no mercado de CDS, e a natureza sistémica daquele mercado. O primeiro estudo analisa a existência de negociação informada no mercado de CDS antes de operações de aquisição, fusões ou venda de ativos relevantes. A nossa análise mostra uma reação dos prémios de CDS antes do anúncio daqueles eventos, sendo em alguns casos mais imediata do que a reação dos mercados acionistas. O segundo estudo avalia o conteúdo informativo das posições em aberto no mercado de CDS utilizando dados em painel de diferentes empresas ao longo do tempo. Os resultados indiciam que as posições em aberto podem ajudar a prever variações futuras dos prémios de CDS e retornos acionistas. Em acréscimo, verifica-se um aumento estatisticamente significativo das posições em aberto antes da divulgação de surpresas negativas nos resultados das empresas. O terceiro estudo mede os efeitos da proibição de posições longas em CDS sobre entidades soberanas pertencentes ao Espaço Único Europeu sem a detenção do ativo subjacente pelo comprador. A análise mostra um efeito negativo da proibição sobre a qualidade do mercado, pese embora se tenha assistido em simultâneo à redução da volatilidade. Por fim, são analisados os determinantes dos montantes associados a posições em aberto, com o intuito de compreender como o mercado de CDS pode influenciar o risco sistémico. Os resultados indicam que a assimetria de informação e a divergência de opiniões dos investidores influenciam aqueles montantes. Todavia, fatores sistemáticos como risco de contraparte, aversão ao risco e risco de re-financiamento parecem ser ainda mais relevantes por via do efeito que exercem no risco do balanço dos intermediários financeiros.